Vertical Motions and Their Effects on a Biogeochemical Tracer in a Cyclonic Structure Finely Observed in the Ligurian Sea. Issue 6 (7th June 2019) - Rousselet, L.; Doglioli, A. M.; de Verneil, A.; Pietri, A.; Della Penna, A.; Berline, L.; Marrec, P.; Grégori, G.; Thyssen, M.; Carlotti, F.; Barrillon, S.; Simon‐Bot, F.; et al.
Abstract: Vertical velocities can be estimated indirectly from in situ observations by theoretical frameworks like the ω ‐equation. Direct measures of vertical exchanges are challenging due to their typically ephemeral spatiotemporal scales. In this study we address this problem with an adaptive sampling strategy coupling various biophysical instruments. We analyze the 3‐D organization of a cyclonic mesoscale structure finely sampled during the Observing Submesoscale Coupling At High Resolution cruise in the Ligurian Sea during fall 2015. The observations, acquired with a moving vessel profiler, highlight a subsurface low‐salinity layer (≃50 m), as well as rising isopycnals, generated by geostrophic cyclonic circulation, in the structure's center. Reconstructed 3‐D fields of density and horizontal velocities are used to estimate the vertical velocity field down to 250 m by applying the adiabatic QG  ω ‐equation, for the first time in this region. The vertical motions are characterized by multipolar patterns of downward and upward velocities on the edges of the structure and significantly smaller vertical velocities in its center. Both the 3‐D distribution of particles (size ≥100 μm), measured with a laser optical plankton counter, and the Synechococcus and Prochlorococcus abundances (cell per cubic meter) measured by flow cytometry are consistent with the 3‐D velocity field. In particular, a secondary vertical recirculation is identified that upwells particles (from 250 to 100 m) along isohalines to the structure's center. Besides demonstrating the effect of vertical patterns on biogeochemical distributions, this case study suggests to use particle matter as a tracer to assess physical dynamics. Key Points: An adaptive sampling strategy allows for fine‐scale observations of biophysical vertical processes inside a cyclonic mesoscale structure Multipolar patterns of intense downward and upward velocities (from adiabatic QG omega‐equation) are identified on the edges of the structure Particle matter appears as a valid tracer of vertical velocities